The role of thymic tolerance in CNS autoimmune disease - Handel, A; Irani, S; Holländer, G (Springer Nature, 2018)
The contributions of the peripheral adaptive and innate immune systems to CNS autoimmunity have been extensively studied. However, the role of thymic selection in these conditions is much less well understood. The thymus is the primary lymphoid organ for the generation of T cells; thymic mechanisms ensure that cells with an overt autoreactive specificity are eliminated before they emigrate to the periphery and control the generation of thymic regulatory T cells. Evidence from animal studies demonstrates that thymic T cell selection is important for establishing tolerance to autoantigens. However, there is a considerable knowledge gap regarding the role of thymic selection in autoimmune conditions of the human CNS. In this Review, we critically examine the current body of experimental evidence for the contribution of thymic tolerance to CNS autoimmune diseases. An understanding of why dysfunction of either thymic or peripheral tolerance mechanisms rarely leads to CNS inflammation is currently lacking. We examine the potential of de novo T cell formation and thymic selection as novel therapeutic avenues and highlight areas for future study that are likely to make these targets the focus of future treatments.